PENGARUH CAPITAL ADEQUACY RATIO TERHADAP RETURN ON EQUITY PADA PERBANKAN NASIONAL PERIODE TAHUN 2020 – 2022 - Wibowo, Bayu Teguh (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
One of the policies to strengthen the Rupiah is to strengthen the financial sector, especially banks. Bank performance and health are the main factors in banking. Performance is shown by Return on Equity (ROE) and bank health is shown by Capital Adequacy Ratio (CAR). Referring to secondary national banking based data on the IDX for 2020 - 2022 and processed using SPSS with simple linear regression analysis, it shows that CAR has a positive and significant effect on ROE